Ultrasonographic Features of Papillary Thyroid Carcinomas According to Their Subtypes - Baek, Hye Jin; Kim, Dong Wook; Shin, Gi Won; Heo, Young Jin; Baek, Jin Wook; Lee, Yoo Jin; Cho, Young Jun; Park, Ha Kyoung; Ha, Tae Kwun; Kim, Do Hun; Jung, Soo Jin; Park, Ji Sun; et al. (Frontiers in Endocrinology, 2018)
Background: The ultrasonographic characteristics and difference for various subtypes of papillary thyroid carcinoma (PTC) are still unclear. The aim of this study was to compare the ultrasonographic features of PTC according to its subtype in patients undergoing thyroid surgery. Methods: In total, 140 patients who underwent preoperative thyroid ultrasonography (US) and thyroid surgery between January 2016 and December 2016 were included. The ultrasonographic features and the Korean Thyroid Imaging Reporting and Data System (K-TIRADS) category of each thyroid nodule were retrospectively evaluated by a single radiologist, and differences in ultrasonographic features according to the PTC subtype were assessed. Results: According to histopathological analyses, there were 97 classic PTCs (62.2%), 34 follicular variants (21.8%), five tall cell variants (3.2%), two oncocytic variants (1.3%), one Warthin-like variant (0.6%), and one diffuse sclerosing variant (0.6%). Most PTCs were classified under K-TIRADS category 5. Among the ultrasonographic features, the nodule margin and the presence of calcification were significantly different among the PTC subtypes. A spiculated/microlobulated margin was the most common type of margin, regardless of the PTC subtype. In particular, all tall cell variants exhibited a spiculated/microlobulated margin. The classic PTC group exhibited the highest prevalence of intranodular calcification, with microcalcification being the most common. The prevalence of multiplicity and nodal metastasis was high in the tall cell variant group. Conclusions: The majority of PTCs in the present study belonged to K-TIRADS category 5, regardless of the subtype. Our findings suggest that ultrasonographic features are not useful for distinguishing PTC subtypes.